Global analysis of entrainment in dialogues - Cabarrão, V.; Trancoso, I.; Mata, A. I.; Moniz, H.; Batista, F. (Advances in Speech and Language Technologies for Iberian Languages. IberSPEECH 2016. Lecture Notes in Computer Science, 2016)
This paper performs a global analysis of entrainment between dyads in map-task dialogues in European Portuguese (EP), including 48 dialogues, between 24 speakers. Our main goals focus on the acoustic-prosodic similarities between speakers, namely if there are global entrainment cues displayed in the dialogues, if there are degrees of entrainment manifested in distinct sets of features shared amongst the speakers, if entrainment depends on the role of the speaker as either giver or follower, and also if speakers tend to entrain more with specific pairs regardless of the role. Results show global entrainment in almost all the dyads, but the degrees of entrainment (stronger within the same gender), and the role effects tend to be less striking than the interlocutors’ effect. Globally, speakers tend to be more similar to their own speech in other dialogues than to their partners. However, speakers are also more similar to their interlocutors than to speakers with whom they never spoke.